The informationist: building evidence for an emerging health profession - Grefsheim, Suzanne F (Medical Library Association, 2010)
BACKGROUND: To encourage evidence-based practice, an Annals of Internal Medicine editorial called for a new professional on clinical teams: an informationist trained in science or medicine as well as information science. OBJECTIVES: The study explored the effects of informationists on information behaviors of clinical research teams, specifically, frequency of seeking information for clinical or research decisions, range of resources consulted, perceptions about access to information, confidence in adequacy of literature searches, and effects on decision making and practice. It also explored perceptions about training and experience needed for successful informationists. METHODS: Exploratory focus groups and key interviews were followed by baseline and follow-up surveys conducted with researchers and clinicians receiving the service. Survey data were analyzed with Pearson's chi-square or Fisher's exact test. RESULTS: Comparing 2006 to 2004 survey responses, the researchers found that study participants reported: seeking answers to questions more frequently, spending more time seeking or using information, believing time was less of an obstacle to finding or using information, using more information resources, and feeling greater satisfaction with their ability to find answers. Participants' opinions on informationists' qualifications evolved to include both subject knowledge and information searching expertise. CONCLUSION: Over time, clinical research teams with informationists demonstrated changes in their information behaviors, and they valued an informationist's subject matter expertise more.